The wonders of the world [dvd] - Thommana, Joseph (Dubai, United Arab Emirates : Al Ghanim Video, 2006)
Journeys around the globe to present the magnificent sights of the natural and human worlds. Covers mountains, rivers, ecosystems, ancient cities, and modern structures in the Alps, Australia, Brazil, Cambodia, Canada, China, Egypt, England, France, Greece, India, Indonesia, Iran, Iraq, Italy, Jordan, Malaysia, Mexico, Morocco, Saudia Arabia, Taiwan, Turkey, United Arab Emirates, USA, Venezuela, and Zimbabwe.
"A world tour to witness the most wonderful sites on the earth : ancient & modern, natural & man-made, forgotten & forth-coming" -- Cover.
Researched & programmed by Joseph Thommana ; narration, Phil Blizzard & Julia Wheeler.
Keywords: Natural monuments; Curiosities and wonders